RETROSPECTIVE ANALYSIS OF RESPIRATORY MEDICATION THERAPY ADHERENCE CLINIC (RMTAC) IN THE MANAGEMENT OF PAEDIATRIC BRONCHIAL ASTHMA - Karniza Khalid; Wan Nor Amalina Zainun; Amalina Anuar; Nurul Azima Mazlan; Nuqman Mursyid Ramli; Ang Wei Chern (Asian Journal of Medicine & Health Sciences, 2021)
Background: Paediatric respiratory medication therapy adherence clinic (RMTAC) serves as an excellent platform for patient-centred care. In most healthcare settings, pharmacists and physicians often do not readily communicate because they work independently and in parallel, rather than collaboratively. Objective: The present study aimed to focus on the roles of RMTAC to complement clinical paediatrics management of bronchial asthma on the provision of clinical assessment, counselling and monitoring. Methods: This retrospective study involved data retrieval of paediatric bronchial asthma patients seen by paediatric RMTAC clinic and those without RMTAC, from 1 January 2019 until 31 December 2020. The study variables of interest were collected, collated and compared, which include the demographic particulars (age, serial weight and height) and information on the assessment of therapy adherence and inhaler technique. Results: A total of 87 clinical records of paediatric bronchial asthma were retrieved for this study (40 with no RMTAC vs. 47 with RMTAC). At the first visit, majority had well controlled asthma (n=37, 42.5%) with low medication adherence (n=26, 29.9%). The assessment of metered-dose inhaler technique was significantly poor without RMTAC monitoring, χ2=43.54, df=1, p<0.001. Univariate analysis determined that age (OR=1.16, 95% CI=1.0-1.3) and good MDI technique (OR=6.4, 95% CI=1.35-30.14) were significantly associated with good asthma control. Conclusion: Our paper highlights the importance of paediatric RMTAC to complement medical management of bronchial asthma. We highly recommend paediatric RMTAC service to be strengthened and introduced throughout all healthcare facilities in Malaysia to improve healthcare delivery.